2012
DOI: 10.1111/exd.12031
|View full text |Cite
|
Sign up to set email alerts
|

Nature versus nurture: does human skin maintain its stratum corneum lipid properties in vitro?

Abstract: Human skin equivalents (HSEs) mimic human skin closely, but show differences in their stratum corneum (SC) lipid properties. The aim of this study was to determine whether isolation of primary cells, which is needed to generate HSEs, influence the SC lipid properties of HSEs. For this purpose, we expanded explants of intact full thickness human skin and isolated epidermal sheets in vitro. We investigated whether their outgrowths maintain barrier properties of human skin. The results reveal that the outgrowths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Since the repeat distance of the LPP in NHS is approximately 13 nm [44], this indicates that the lamellar organization of CC-FTMs resembles that of NHS to a higher extent but still not completely. Moreover, the additional unknown lamellar phase in FTMs, possibly explained by phase separated CERs, is not present in CC-FTMs and NHS [8].…”
Section: Discussionmentioning
confidence: 99%
“…Since the repeat distance of the LPP in NHS is approximately 13 nm [44], this indicates that the lamellar organization of CC-FTMs resembles that of NHS to a higher extent but still not completely. Moreover, the additional unknown lamellar phase in FTMs, possibly explained by phase separated CERs, is not present in CC-FTMs and NHS [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the orthorhombic packing cannot be reproduced in vitro under conditions described in this study. Only a hexagonal lateral packing was observed in the 2 nd and 3 rd generation outgrowths, similar to other epidermal and full thickness HSEs [12,[25][26][27]. The abundant formation of a hexagonal packing in culture may be explained by: a reduction in SC FFAs levels and in their chain lengths or by an increase in the relative levels of MUFAs [28].…”
Section: Discussionmentioning
confidence: 64%
“…Our previous studies showed that the 1 st generation Ex-HSEs do not fully maintain SC lipid properties as in native human skin [12]. Therefore, we investigated whether passaging to the 2 nd and 3 rd generation results in SC lipid properties similar to the 1 st generation.…”
Section: Orthorhombic Lateral Packing Is Gradually Lost With Increasimentioning
confidence: 96%
See 1 more Smart Citation
“…with Graftskin with compression was significantly more effective in achieving complete wound closure at 8 weeks (AST2000) CellSystems Biotechnologie, GmbH (Germany) It is a full-layer human skin model consisting of fibroblasts as a basal skin layer and keratinocytes as the epidermis Leiden epidermal skin model for the assessment of skin condition after its exposure to aggressive chemical agents Thakoersing, Bouwstra et al [161,162], and EI Ghalbzouri [163] (Netherlands) It is a full-layer human skin model consisting of fibroblasts in 3D collagen matrix as a basal skin layer and keratinocytes as the epidermis…”
Section: Venous Leg Ulcersmentioning
confidence: 99%